2003
DOI: 10.1021/la0342767
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Langmuir Monolayers of the Amphiphilic Ru Complex at the Air/Water Interface by Ultraviolet Photoelectron Yield Spectroscopy

Abstract: Ultraviolet photoelectron yield spectroscopy (UPYS) was applied to the characterization of Langmuir layers of the amphiphilic Ru complex at the air/water interface in ambient conditions. The UPY spectra were successfully obtained for Langmuir layers of the complex in the surface concentration range of 0.14−2.1 molecule nm-2, and the photoelectron emission threshold energy, E t, and photoelectron emission efficiency, α, were determined for the respective surface concentrations. The E t value was constant at low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Adsorption and organization of metallosurfactants at interfaces is central to the development of a range of hybrid materials, thin-film devices, and heterogeneous catalysts. , Accordingly, the interest in these materials has initiated a number of structural studies of the micelles and thin-film structures formed by metallosurfactants as the numerous potential applications depend intimately on the relationship between molecular structure and packing ability. Since metallosurfactants offer a great deal of flexibility in their molecular design, this relationship between structure and function can, in principle, be tailored.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption and organization of metallosurfactants at interfaces is central to the development of a range of hybrid materials, thin-film devices, and heterogeneous catalysts. , Accordingly, the interest in these materials has initiated a number of structural studies of the micelles and thin-film structures formed by metallosurfactants as the numerous potential applications depend intimately on the relationship between molecular structure and packing ability. Since metallosurfactants offer a great deal of flexibility in their molecular design, this relationship between structure and function can, in principle, be tailored.…”
Section: Introductionmentioning
confidence: 99%
“…Among the transition-metal complexes studied in LB films, ruthenium(II) bipyridyl complexes have received considerable attention, [30][31][32][33][34] owing to their rich photo-and electrochemical behavior, [35,36] diversity of coordination forms, [37] high thermal and chemical stability, and high solubility in common solvents. LB films of different ruthenium complexes have already successfully been applied in high-performance sensors [38][39][40][41] and been shown to exhibit second harmonic generation activities.…”
mentioning
confidence: 99%
“…Monjushiro et al reported that no photoemission was observed from pure water. 13 The photoemission spectrum of the pure water surface, which is shown in Fig. 3, exhibits the same trend.…”
Section: Resultsmentioning
confidence: 58%
“…It has been reported that PYSA is applicable to the in situ characterization of Langmuir layers of photosensitive molecules at the air/water interface in ambient conditions. 13 In this study, we applied PYSA to photoemission experiments on liquids, focusing on components in beverages, under the same conditions as our living environment.…”
Section: Introductionmentioning
confidence: 99%